1997
DOI: 10.1007/s004320050107
|View full text |Cite
|
Sign up to set email alerts
|

Increased number of cancer cells in bronchial washing fluid detected by combining conventional cytology and high-resolution flow cytometry

Abstract: The present study was performed to improve early lung cancer diagnosis in bronchial washing fluid, thereby increasing the diagnostic sensitivity of bronchoscopy by means of high-resolution flow cytometry (FC). We combined dual-parameter DNA/protein FC and conventional cytology in bronchial washing fluid samples from 112 patients with neoplastic and non-neoplastic lung diseases and found 43% of histologically confirmed tumor cases to be cytologically positive; 63% of the tumor samples were aneuploid, 52% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

1998
1998
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
1
0
0
1
Order By: Relevance
“…The present data demonstrated that the detection of cells with increased DNA fluorescence can be improved using DNA/protein measurements simultaneously. This fact is well documented by our previous results, which clearly showed that a second FC parameter increases the detectability of small DNA abnormalities (22,31,32). The fact that such small near diploid clones were also observed during follow-up (data not shown) makes them very unlikely to be due to artifacts or to technical problems.…”
Section: Discussionsupporting
confidence: 86%
“…The present data demonstrated that the detection of cells with increased DNA fluorescence can be improved using DNA/protein measurements simultaneously. This fact is well documented by our previous results, which clearly showed that a second FC parameter increases the detectability of small DNA abnormalities (22,31,32). The fact that such small near diploid clones were also observed during follow-up (data not shown) makes them very unlikely to be due to artifacts or to technical problems.…”
Section: Discussionsupporting
confidence: 86%
“…São elas: a biópsia transbrônqui-ca e a punção aspirativa transbrônquica por agulha (17) . A associação de todos esses métodos aumenta de maneira significativa o rendimento do exame (18) .…”
Section: Broncofibroscopiaunclassified